COVID 19 era: a beginning of upsurge in unwanted pregnancies, unmet need for contraception and other women related issues. (3rd July 2020) - Kumar, Naina
Abstract: The Novel Coronavirus disease that was first identified in Wuhan city of China in December 2019 has emerged as one of the fastest spreading pandemics all over the world affecting millions of people and causing millions of deaths worldwide. In an attempt to control its spread, countries have imposed local and national lockdowns, affecting many healthcare services, especially sexual and reproductive health services which are actually essential and lifesaving. In near future this will result in a large number of grave consequences including increased unmet need for modern contraceptives, unintended pregnancies, increased unsafe abortions, maternal and neonatal deaths and other harmful practices like female genital mutilation and child marriages in developing countries. The present short review focusses on such issues which will be dramatically increased depending on the duration of lockdowns and the time for which the sexual and reproductive health services will remain halted. It also reflects the need for considering reproductive health services as essential, allowing the people to avail these services without any fear and hence, saving many more lives which will be lost not due to coronavirus infection. Methodology : The data was searched from various governmental and non-governmental organisation sites including the World Health Organisation, United Nations, United Nations Population Fund, Guttmacher Institute and many PubMed indexed journals.